Faith and work : Christian perspectives, research and insights into the movement - Ewest, Timothy (Emerald Publishing Limited : IAP, Information Age Publishing, Inc., 2018)
Those who adhere to a faith tradition are longing for theories and insights into how they can be true to their faith within the workplace and yet be sensitive and respectful to others of varying faith commitments and beliefs. Yet for Christians, respect of other faith traditions is especially difficult since Christianity as the dominate religion has become secularized and institutionalized within the workplace as represented in holidays and days off. Within the multiple theoretical and research dimensions of management, religion and spirituality, this book explores theoretical, conceptual and strategic theories and research which consider how individuals and organizations integrate their Christian faith in the workplace, and how these groups attempt to change society as a whole. This historical movement is characterized by a desire for people to live a holistic life which integrates their Christian faith into the workplace, also deemed "faith at work""-- Provided by publisher.
Keywords: Employees -- Religious life.; Work -- Religious aspects -- Christianity.; Religion -- Spirituality.; Spirituality and religious experience.; elektronické knihy; electronic books